The Effect of Heart Exercise to Blood Pressure on Elderly with Hypertension at PSTW Pagar Dewa Bengkulu City - Devi Listiana; Buyung Keraman; Kurnia Esti (Jurnal Sains Kesehatan, 2019)
Healthy heart exercises can be used as non-pharmacological therapy in the treatment of hypertension. The aims of this study to determine Effect of Heart Exercise to Blood Pressure on Elderly with Hypertension at PSTW Pagar Dewa Bengkulu City. Design of this study was Pre-Experimental Design with Pre-Test and Post-Test Group Design, observation design which was conducted twice, that were before and after the experiment. Aneroid sphgmomanometer measuring devices, stethoscopes and digital tension and measuring methods by measuring blood pressure elderly. Population in this study were all the elderly who had hypertension were in PSTW Pagar Dewa Bengkulu City, with the amounted of 44 people and the sample used according to criteria was 26 people. Data analysis used the Wilcoxon Signed-Rank Test. The results of this study have an influence, obtained Systolic Blood Pressure values in the Elderly before and after Healthy Heart exercised Z = -4,282 with p = value = 0,000 0.05 means significant diastolic Blood Pressure in the Elderly before and after Healthy Heart exercised  Z = - 4,314 with p = value = 0,000 0.05 means significant. Suggestions elderly who suffer from hypertension can used healthy heart exercises as non-pharmacological therapy. Keywords: elderly, heart exercises, hypertension